xperience with the pericardial window for the diagnosis of precordial lesions. Hospital Universitario del Valle, 1983-1987 (Colombia Medica, 1988)
The records of 441 patients with penetrating precordial wounds managed during the period January 1983 to December 1987, 5 years of initiating a selective management of precordial wounds at the Hospital Universitario del Valle, in Cali, using a pericardial window technique as a diagnostic method were reviewed. A total of 113 patients underwent immediate thoracotomy due to cardiac tamponade and or severe hypovolemic shock. The remaining 328 patients were treated with subxyphoid pericardial window, positive in 74 patients and negative in 251. The latter corresponds to an equal number of unnecessary thoracotomies avoided with the reported selective management. Our results allow us to question the extended concept that thoracotomy is mandatory for every patient with precordial wounds. Five complications: one wound infection, four pneumothorax, and one pericarditis.